Identidades secretas: representações do negro nas Histórias em quadrinhos norte-americanas - Lopes, Romildo Sergio [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Thinking of the comicsas a vehicle of mass communication, whose modern history crossed through all twentieth century until contemporary times, keeping his language almost unchanged, it is possible to infer about the great strength of the medium and, consequently, the large impacts of the representations it creates and circulates through society by then. The purpose of this paper is to discuss the identities of the black American in the comics of Marvel Comics, published in Brazil. We have as hypothesis, how such representations can create identification with models of conformity or reinforce prejudicies through the classic stereotypes of racional minority in the United States. We have applied as methodology a junction of two fields; a Pierce's semiotic matrix, as a research technique to reveal the representations and their arguments, as well as sociology, which drew on the notions of culture and identity explored by Stuart Hall and Anthony Giddens for analysis of results. The samples comes from Marvel Comics magazines published by Panini, in the period from July 1 to December, 2011, in a collection purchased at news stands and specialized shops. Totaling 76 magazines, with 252 analyzed stories which form identified significant shareholdings of 1370 characters, among these only 75, or 5,47% were managed by blacks, demonstrating a low representation. This percentage is actually the remnant which is the research corpus. 16 black important chacters were identified, those would be grouped into five possible models of identities many of them are related to other fields such as cinema and music. As a whole, we can say thay the two characters that are compared to positive models and are more polyphonic, are Storm and Luke Cage. However, the low representativeness and excess characterization make comics analyzed at, a very fertile field identification by the Brazilian public

Pensando as histórias em quadrinhos enquanto veículo de comunicação de massa, cuja história moderna atravessou por todo século XX até chegar à contemporaneidade, mantendo sua linguagem quase que inalterada, é possível inferir sobre a grande força do meio e, consequentemente, grande impacto das representações que elas criam com quem circulam pela sociedade. A proposta desse trabalho é discutir quais são as identidades do negro nas histórias em quadrinhos americanas da editora Marvel Comics publicadas no Brasil. Temos por hipótese o quanto tais representações podem criar identificação com modelo de conformidade ou reforçar preconceitos por meio dos estereótipos clássicos de minoria racial nos Estados Unidos. A metodologia aplicada é a junção de dois campos, a semiótica aplicada é a junção de dois campos: a semiótica de matriz pierciana, enquanto técnica de pesquisa, responsável por dar relevo às representações e a seus argumentos, bem como a sociologia, a qual se valeu das noções de cultura e identidade explorados por Stuart Hall e Anthony Giddens para as análises dos resultados. A amostra parte de uma coleção de revistas da Marvel Comics publicadas no Brasil pela Panini, no período de 01 de julho a 31 de dezembro de 2011, adquiridas nas bandas e lojas especializadas, perfazendo 76 revistas, com 252 histórias analisadas em que foram identificadas 1370 participações relevantes dos personagens, dessas apenas 75, ou seja, 5,47% foram geridas por negros, demonstrando uma baixa representatividade. Essa percentagem constitui de fato o recorte que é o corpus da pesquisa. Nele, identificamos 16 personagens negros relevantes que, poderiam ser agrupados em 5 modelos possíveis de identidades, muitas das quais alinhadas aos demais campos como cinema e música. Por conclusão, podemos dizer que os dois personagens que se alinham com modelos positivos e mais polifônicos são Tempestade e Luke Cage. Contudo a...
Secret identities: representations of black in North American comics
Keywords: Histórias em quadrinhos; Negros; Identidade; Comunicação; Comic books, strips, etc